Features of the New Regulatory Framework for Preventing the Manipulation of Financial Markets in the European Union - Asenov, Emil (Research Papers, 2017)
The dissemination of false or misleading information can have a significant impact on the prices of financial instruments. Manipulation can cause significant losses for all participants in financial markets. The assessment of regulatory frameworks and practices showed that the systems of criminal and administrative sanctions applied in the European Union are weak and heterogeneous as a whole. The execution of adequate prevention against manipulative actions in the future requires the implementation of measures with organizational, technological and legal nature. An extremely important measure is the introduction of common thresholds for manipulative behavior, which is considered to be particularly unacceptable, and the criminalization of the most serious forms of market manipulation. This approach will give a clear signal to the public as well as to the potential offenders that the EU authorities will conduct more effective prevention of market abuses in the future. The normative analysis of the elements of the new regulatory framework indicates sufficient grounds to assume that it creates the necessary preconditions to achieve a higher degree of effectiveness of prevention against manipulation practices in the financial markets in the European Union.